2015
DOI: 10.1002/poc.3448
|View full text |Cite
|
Sign up to set email alerts
|

The DFT study on non‐conjugated polymer host materials based on styrene derivatives for phosphorescent polymer light‐emitting diodes

Abstract: A series of poly(4,4-vinyltriphenylamine) based non-conjugated polymer as host molecules are designed and studied by density functional theory. The results show that the substituent has a great influence on the properties of polymer. The parent molecule directly linked para-carbazole, β-pyrrole and triphenylamine are favorable to hole injection, and para-carbazole could significantly increase E T of the host molecules. The large changes of structural parameters between the lowest triplet state and ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…As shown in Figure , in such host−guest systems, the singlet excitation energies of all host molecules are higher than the relevant guest. The formation of singlet excitons generated on the guest is mainly from singlet excitons on the host via S−S FET; the formation of triplet excitons originate from both triplet excitons on the host molecule via T−T DET mechanism and singlet excitons via intersystem crossing (ISC) to the guest . In this context, POSTF and SOSTF with better performance are selected as the host materials for blue PhOLEDs.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , in such host−guest systems, the singlet excitation energies of all host molecules are higher than the relevant guest. The formation of singlet excitons generated on the guest is mainly from singlet excitons on the host via S−S FET; the formation of triplet excitons originate from both triplet excitons on the host molecule via T−T DET mechanism and singlet excitons via intersystem crossing (ISC) to the guest . In this context, POSTF and SOSTF with better performance are selected as the host materials for blue PhOLEDs.…”
Section: Resultsmentioning
confidence: 99%
“…On the whole, the NTO analyses are in good agreement with the spin density distributions. Many literature reports 47,48 have indicated that large structural distortions between the ground and the triplet states would lead to an increase of the non-radiative transition rate (k nr ) that might cause unfavorable energy loss. The nonradiative decay rate constant (k nr ) from triplet state to ground state can be evaluated according to eqn (3): 48,49…”
Section: Triplet Energymentioning
confidence: 99%